2012
DOI: 10.1177/183693911203700413
|View full text |Cite
|
Sign up to set email alerts
|

Active versus Passive Screen Time for Young Children

Abstract: IN THIS PAPER WE REPORT SOME initial findings from our investigations into the Australian Government's Longitudinal Study of Australian Children dataset. It is revealed that the majority of Australian children are exceeding the government's Screen Time recommendations and that most of their screen time is spent as TV viewing, as opposed to video game play or computer use. In light of this finding, we review the body of research surrounding children's engagement in Screen Time activities and the associated posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 21 publications
0
64
0
3
Order By: Relevance
“…An Australian study of thousands of children who were randomly sampled found that two to three year old children spent a mean of almost two hours a day of screen time during weekdays in 2006, but there were no reports of videogame or computer time for that age group. For three to four year olds, weekday videogame and computer time averaged 6 and 17 minutes a day respectively in 2007 [30]. Note that this study predates the wide adoption of tablets.…”
Section: Screens Computers and Young Childrenmentioning
confidence: 94%
See 1 more Smart Citation
“…An Australian study of thousands of children who were randomly sampled found that two to three year old children spent a mean of almost two hours a day of screen time during weekdays in 2006, but there were no reports of videogame or computer time for that age group. For three to four year olds, weekday videogame and computer time averaged 6 and 17 minutes a day respectively in 2007 [30]. Note that this study predates the wide adoption of tablets.…”
Section: Screens Computers and Young Childrenmentioning
confidence: 94%
“…Their conclusion is both reasonable and not surprising in that children's use of technology can have positive, neutral, or negative impacts, depending on what technology is used, and how it is used. Sweetser et al [30] delved further into the different kinds technology by distinguishing between passive screen time, and active screen time. Among types of active screen time, they mentioned physically active screen time, which includes playing videogames that involve children moving (e.g., Nintendo Wii).…”
Section: Families and Their Use Of Technology Chi 2015 Crossings Sementioning
confidence: 99%
“…It was found that 90% of children had a computer and between 93% and 97% played computer games. Using data from the same study, Sweetser et al (2012) found that the mean time for using the computer/playing video games per week for children at age 8 -9 was 2 hours and 23 minutes. This steadily increased to 2 hours 52 minutes at age 9 -10 (2009 data) and 3 hours 13 minutes at age 10-11 (2010 data).…”
Section: Introductionmentioning
confidence: 93%
“…However, the AAP primarily used research centered on traditional screen media to draw its conclusions about the potential harmful consequences of screen time. Traditional screen media is different than mobile media in that traditional screen media often encourages passive, non-interactive consumption of media (Sweetser, Johnson, Ozdowska, & Wyeth, 2012). A growing number of early childhood scholars and organizations, including the National Association for the Education of Young Children (NAEYC) and the Fred Rogers Center for Early Learning and Children's Media (2012) have differentiated between the passive screen time the AAP position statements were built upon and active screen time.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Cognitively active screen time: Use of screen media that encourages problem solving and creative thinking (Sweetser et al, 2012).…”
Section: Operational Definitionsmentioning
confidence: 99%